Aberrant SOX10 and RET expressions in patients with Hirschsprung disease - Gunadi; Verrell Christopher Amadeus; Fadila Dyah Trie Utami; Fiqih Vidiantoro Halim; Nabilah Anisa Novebri; Rahaditya Alrasyidi Hanggoro; Avinindita Nura Lestari; Kristy Iskandar; Andi Dwihantoro; Eko Purnomo (BMC Pediatrics, 2024)
Abstract Background HSCR is a complex genetic disorder characterized by the absence of ganglion cells in the intestine, leading to a functional obstruction. It is due to a disruption of complex signaling pathways within the gene regulatory network (GRN) during the development of the enteric nervous system (ENS), including SRY-Box Transcription Factor 10 (SOX10) and REarranged during Transfection (RET). This study evaluated the expressions of SOX10 and RET in HSCR patients in Indonesia. Methods Total RNA of 19 HSCR ganglionic and aganglionic colons and 16 control colons were analyzed using quantitative real-time polymerase chain reaction for SOX10 and RET with GAPDH as the reference gene. Livak’s method (2−ΔΔC T) was used to determine the expression levels of SOX10 and RET. Results Most patients were males (68.4%), in the short aganglionosis segment (78.9%), and had undergone transanal endorectal pull-through (36.6%). There were significant upregulated SOX10 expressions in both ganglionic (2.84-fold) and aganglionic (3.72-fold) colon of HSCR patients compared to controls’ colon (ΔCT 5.21 ± 2.04 vs. 6.71 ± 1.90; p = 0.032; and ΔCT 4.82 ± 1.59 vs. 6.71 ± 1.90; p = 0.003; respectively). Interestingly, the RET expressions were significantly downregulated in both ganglionic (11.71-fold) and aganglionic (29.96-fold) colon of HSCR patients compared to controls’ colon (ΔCT 12.54 ± 2.21 vs. 8.99 ± 3.13; p = 0.0004; and ΔCT 13.90 ± 2.64 vs. 8.99 ± 3.13; p = 0.0001; respectively). Conclusions Our study shows aberrant SOX10 and RET expressions in HSCR patients, implying the critical role of SOX10 and RET in the pathogenesis of HSCR, particularly in the Indonesian population. Our study further confirms the involvement of SOX10-RET within the GNR during the ENS development.